Simultaneous compared to interval administration of mifepristone and misoprostol for medical abortion up to 10+0 weeks' gestation: a systematic review with meta-analyses. Issue 4 (20th February 2020) - Schmidt-Hansen, Mia; Lord, Jonathan; Hasler, Elise; Cameron, Sharon
Abstract : Background: Medical abortion with mifepristone and misoprostol usually involves an interval of 36–48 hours between administering these drugs; however, it is possible that the clinical efficacy at early gestations may be maintained when the drugs are taken simultaneously. The objective of this systematic review was to determine the safety and effectiveness of simultaneous compared with interval administration of mifepristone and misoprostol for abortion up to 10 +0 weeks' gestation. Methods: We searched Embase Classic, Embase; Ovid MEDLINE(R) including Daily, and Epub Ahead-of-Print, In-Process & Other Non-Indexed Citations; and Cochrane Library on 11 December 2019. We included randomised controlled trials (RCTs), published in English from 1985, comparing simultaneous to interval administration of mifepristone and misoprostol for early abortion. Risk of bias was assessed using the Cochrane Collaboration checklist for RCTs. Meta-analysis of risk ratios (RRs) using the Mantel-Haenszel method were performed. The quality of the evidence was assessed using GRADE. Results: Meta-analyses of three RCTs (n=1280) showed no differences in 'ongoing pregnancy' (RR 1.78, 95% CI 0.38 to 8.36), 'haemorrhage requiring transfusion or ≥500 mL blood loss' (RR 0.11, 95% CI 0.01 to 2.03) and 'incomplete abortion with the need for surgical intervention' (RR 1.30, 95% CI 0.76 to 2.25) between the interventions. Individual study results showed no difference in patient satisfaction, or 'need for repeat misoprostol', although 'time to onset of bleeding or cramping' was longer after simultaneous than interval administration. The quality of evidence was very low to moderate. Conclusion: The published data support the use of simultaneous mifepristone and misoprostol for medical abortion up to 9 +0 weeks in women who prefer this method of administration.